LESSON STUDY IMPROVE LITERACY SCIENCE IN ELEMENTARY SCHOOL FOR SOCIETY 5.0 - Syarif, Muhammad Ilham; Fachrudin, Farida (Jurnal Bahana Manajemen Pendidikan, 2017)
Lesson study can be implemented for teachers to improve the quality of integrated science learning in elementary schools. Through lesson study the teacher can provide input and improve the quality of learning that has been neglected. Lesson Study methods is Qualitative research. Result is teacher with lecturers made lessonÂ  Integrated science learning is a science learning that connects concepts with concrete situations in everyday life including social context, Indonesian language context including art culture, context of moral / citizenship education, and mathematical.